Maisy's show : a Maisy pull-the-tab and pop-up book - Cousins, Lucy (My friend Maisy, 2010)
Provides a behind-the-scenes look as Maisy and her friends make costumes, paint scenery, and practice for a big show that will include music, magic tricks, and dancing. Includes pull-tabs and a pop-up scene.